New cyathealean tree fern, Yavanna chimaerica gen. et sp. nov., from the Early Cretaceous of Livingston Island, Antarctica - Vera, Ezequiel Ignacio (Cretaceous Research)
A new genus and species of cyathealean fern, Yavanna chimaerica gen. et sp. nov., is erected for several permineralized stems recovered from the Early Cretaceous (Aptian) Cerro Negro Formation, which crops out at the South Shetland Islands, Antarctica. The new species is characterized by solenostelic erect stems with medullary bundles traversing the pith, and surrounded by persistent petiole bases and adventitious roots. Proximal petiole bases present a one-parted modified omega-shaped trace, which becomes three-parted distally. The anatomy of the new fern show similarities with both Thyrsopteris elegans Kunze and with the Cyatheaceae s.s., suggesting that it is a representative of an extinct lineage among the Cyatheales. Fil: Vera, Ezequiel Ignacio. Universidad de Buenos Aires. Facultad de Cs.exactas y Naturales. Departamento de Geologia. Cat.de Paleontologia; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales; Argentina